2017
DOI: 10.1136/bmjopen-2016-015415.185
|View full text |Cite
|
Sign up to set email alerts
|

185: Knowledge Translation (Kt) and Evidence-Based Medicine (Ebm): A Practical Conflict

Abstract: Background and aimsKnowledge translation (KT) tries to bridge the gap between knowledge production and consumption by targeting the knowledge users and shortening the period of conveying research results to practice. Evidence based medicine (EBM) is the righteous use of accumulated evidence to guide clinical decisions. Therefore, while KT tools are designed to expedite consumption of newly carried-out research, conscientious use of conducted research is hinted at EBM studies. Thus, the primary goal of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In Iran, the researchers in this field are still engaged in conceptualization, theorizing, and modeling for the translation of knowledge, and therefore, there is an argument that the translation of knowledge has not yet matured enough for general application in practice or has not yet been sufficiently introduced in society. [ 7 ] Studies that have examined the status of knowledge translation in Iran have shown that normal approaches to producing and publishing research results in journals, which are passive efforts, are prevalent in the country. [ 3 ] In Iran, the status of knowledge translation in many universities medical sciences in the fields of producing evidence that can be used in decision making, identifying the needs of the audience, and turning it into research projects and the application of research results by end users is far from its desired status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Iran, the researchers in this field are still engaged in conceptualization, theorizing, and modeling for the translation of knowledge, and therefore, there is an argument that the translation of knowledge has not yet matured enough for general application in practice or has not yet been sufficiently introduced in society. [ 7 ] Studies that have examined the status of knowledge translation in Iran have shown that normal approaches to producing and publishing research results in journals, which are passive efforts, are prevalent in the country. [ 3 ] In Iran, the status of knowledge translation in many universities medical sciences in the fields of producing evidence that can be used in decision making, identifying the needs of the audience, and turning it into research projects and the application of research results by end users is far from its desired status.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all the stakeholders in developed and developing countries involved in healthcare decision making face the challenges of knowledge translation to promote the use of evidence. [ 7 ] Lack of resources, especially in the developing countries, is important. The knowledge translation to improve healthcare decision making with the correct use of research results has increased.…”
Section: Introductionmentioning
confidence: 99%